SISTEM PERSEDIAAN STOK BARANG MENGGUNAKAN METODE AGILE BERBASIS WEB PADA BENGKEL THO’BONE - SHANTIKA; Erick Irawadi Alwi; St. Hajrah Mansyur (LPPM Universitas Abdurrab, 2026)
Inventory management at Bengkel Tho’Bone was previously conducted manually, which often resulted in data inconsistencies, delays in stock monitoring, and difficulties in generating accurate inventory reports. This study aims to design a web-based inventory management system using the Agile method as a software development approach to improve efficiency and accuracy in stock management. The study applies the CodeIgniter framework as the system development framework because it adopts the Model–View–Controller (MVC) architecture, which facilitates the separation of business logic, user interface, and data processing. The system development process is carried out through the stages of planning, design, development, testing, and evaluation, which are performed repeatedly according to user requirements. The system is designed to assist administrators and staff in managing item data, suppliers, as well as incoming and outgoing stock transactions. The results show that the developed system is capable of automating stock recording, providing restock notifications when inventory reaches the minimum threshold, and generating structured and easily accessible inventory reports. The implementation of this system improves operational efficiency, reduces human error, and enhances transparency in inventory management. Overall, the application of a web-based inventory management system using the Agile approach and the CodeIgniter framework has proven effective in optimizing inventory control and supporting accurate decision-making at Bengkel Tho’Bone.